Judging in a Mismatch: The Ethical Challenges of Pro Se Litigation. (2nd January 2018) - Henschen, Beth
Abstract : Over the past two decades, U.S. courts have experienced a significant increase in the number of pro se litigants. With the pro se phenomenon has come new ways of thinking about the meaning of justice, fairness, neutrality, and impartiality in the legal system. The traditional notion of a judge as neutral arbiter between two opposing parties in an adversarial process does not fit the reality of pro se litigation, especially when a self-represented party is opposed by one who comes to court with an attorney. Consideration is given to the way in which judges' role orientations are shaped by this situational context. Placed within a framework of judicial goals, judges' statements provide important insights into the approaches they take when they are faced with a mismatch. While ethical guidelines for judges in pro se litigation are evolving, judges continue to confront the challenge of performing their roles in ways that ensure the integrity of the court is not compromised.